Utilizing Static Pricing to Boost Room Revenue in Archipelago International Indonesia Hotels Group - Ni Made Dwi Yulianti; I Ketut Budarma; Gede Ginaya (International Journal of Travel, Hospitality and Events, 2024)
Purpose: This research examines the implementation of static rates to increase room revenue at Archipelago International Indonesia Hotels Group. While the majority of Archipelago International management considers that dynamic rates are more effective at increasing room revenue, the impact of global economic events such as the Covid-19 pandemic, wars, and earthquakes (force majeure) has been underestimated. Static rates can be used to respond to economic downturns induced by these occurrences, which reduce demand. Research methods: This research uses qualitative research methodologies to assess current practices and offer ideal static rate models. It is supported by three concepts and theories: static rates, room revenue, and hotel management. This research also uses tourism economy and revenue management as theoretical foundations. Results and discussion: The findings highlight suboptimal implementation challenges and propose two models at Archipelago International Indonesia Hotels Group: (1) Static Rates Stand Alone: managed by the channel manager for a minimum two-night stay, beneficial for remote or pre-opening hotels, during low occupancy or economic downturns; and (2) Bundle Packages: combining room rates with other services to increase revenue and promote additional facilities. Implication: These models provide consistent pricing, improved forecasting, and increased brand awareness. Implementing these models can help Archipelago International optimize its revenue plans and financial performance.